Implementing Problem Based Learning Strategies to Optimize Science Instruction for Learner Engagement - Shahbodin, Faaizah; Che Ku Mohd, Che Ku Nuraini; Munir, Munir (Journal of Advanced Research Design, 2025)
This paper presents the development of the C2HADAM multimedia courseware prototype, employing a Problem-Based Learning (PBL) approach for teaching Science to Form Two students in selected Malaysian secondary schools. Despite the recognized benefits of Problem-Based Learning (PBL) in enhancing student engagement and understanding in the Science course, there is a lack of multimedia courseware that effectively integrates PBL with constructivist, collaborative, inquiry-based, and exploratory learning principles for Form Two students in Malaysian secondary schools. The paper begins by outlining the theoretical and conceptual frameworks that inform the architecture of C2HADAM, emphasizing the application of renowned learning theories such as constructivism and collaborative learning, as well as PBL itself. Additionally, C2HADAM incorporates principles of inquiry-based learning, simulations, exploratory learning, and a student-centred approach. Further, the paper delineates the life cycle of the courseware’s development, which includes phases of analysis, design, development, implementation, and evaluation. In conclusion, the paper presents testing results from assessing the courseware’s effectiveness.